The Effect of Public Service Quality, Work Discipline, and Organizational Culture on Community Satisfaction - Rulianti, Erina; Nurpribadi, Giri (Yayasan Ilomata, 2024)
The purpose of this study was to determine the effect of Quality of Public Services, Work Discipline, and Organizational Culture to Community Satisfaction. The population in this study were the people of Waluya Village who already had KTPs in hamlet II with a total of 833 family cards. Sampling using the Slovin method with a sample of 270 respondents. The data collection technique used a questionnaire distributed to respondents. Questions in the questionnaire were scored on a Likert scale of 1-5. The data analysis used is multiple linear regression analysis. The results of the regression analysis in this study indicate that partially or simultaneously, the quality of public services, work discipline, and organizational culture have a positive and significant effect on community satisfaction. Simultaneously improving the quality of public services, employee discipline, and good organizational culture will have a positive impact on increasing community satisfaction.